PEREMPUAN ORANG TUA TUNGGAL DALAM PELAKSANAAN FUNGSI KELUARGA DI KECAMATAN DUMAI SELATAN KOTA DUMAI - Syahmala, Nunung; Asriwandari, Hesti (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
Family is small unit in society and it is social unity that has blood relationship and each of the member has act based on the function. A family cereated because there is a marriege between man and woman who both of them agree to get live together and grow up their children who will given birth. In this research will discuss about “ Single Parent Implementing Family Function in south Dumai District Dumai City “ with using descriptive cualitative research method with using sampling purposive technic. The purpose of this research is to know act of woman as single parent in implemeting family function economy level. In this research will know that each af single parent has kinds of way to fulfill all of economy necessary and background of different culture society and view each culture to a divorce. In this research single parent nas to work to fulfill family economy necessary and spare her time between job and care her children. Altough a single parent works as mpek-mpek saler , teacher of recite Al-Qur’an, course teacher and house maid, she has time for her children altough for caring the children family action is needed to help when their mother go to workKey words : Single Parent, Economy, Family, Society Culture